Involvement of Internal Human Resource Organizations Perfomance Measurement in the Public Sector - Natasha Salsabila Utomo; Vishnu Juwono (Budapest International Research and Critics University, 2022)
Today's public sector organizations operate in a dynamic environment that forces organizations to adapt to changing environmental conditions. Organizational performance measurement is understood as one of the functions of management, but is currently being analyzed as a branch of science that develops independently. In order to measure the performance of public sector organizations, it is very important to apply appropriate performance measurement methods. Strategic human capital development must take into account the organization's specific educational background, job-specific experience, and job-specific experience, and that human capital must also be valuable, rare and not easily imitated. The development of human capital has a positive effect on organizational performance. Have a highly specific skilled workforce for certain jobs, to generate higher rents unless there is a match between culture and human resources. When a performance measurement system is adapted to an organization in the public sector, it is important to differentiate the focus of the mission, include all stakeholders in the organization, and emphasize the importance of human resources. HRD practitioners in the public sector should develop more sophisticated plans to create a learning culture that encourages independence and can have a positive impact on civil servant career satisfaction and ultimately organizational effectiveness. Many public sector studies regard rewards for achievement, including salaries and other benefits, such as pensions, as incentives or disincentives for productivity. Therefore, more than one performance measurement method can be chosen for performance measurement in the public sector.